Groundwater Quality Assessment Using Hydrochemical and Multivariate Approaches in Coastal Taluka Shaheed Fazil Rahu, District Badin, Sindh, Pakistan - Ghulam Murtaza Arain; Tarique Mahmood Noonari; Nazia Sattar; Sumaira Khatoon; Nabeel Ali Khan; Nadeem Gul; Muhammad Afzal Jamali (International Journal of Economic and Environmental Geology, 2025)
Pakistan ranks 14th among the most water-stressed countries globally, with groundwater (GW) serving as the primary water source for both rural and urban populations. However, GW contamination is a growing concern, driven by excessive agrochemical use, improper wastewater disposal, and toxic elements. Coastal Sindh, particularly District Badin, faces severe water scarcity and deteriorating GW quality, exacerbated by seawater intrusion and the absence of proper water storage and supply infrastructure. This study assesses GW quality in Taluka Shaheed Fazil Rahu (SFR), District Badin, using hydrochemical and multivariate statistical approaches to evaluate contamination sources and freshwater availability. A total of 105 GW samples were acquired from communal bore wells across three union councils and analyzed for physical, chemical, and microbiological parameters. Results showed that 65.71% of samples exceeded turbidity limits, 64.76% had high EC, and 58.1% surpassed TDS thresholds. Microbiological analysis detected total coliforms in 29.52% and E. coli in 12.38%, indicating fecal contamination. Contaminants followed the order: Cl⁻ (56.19%) > HCO₃⁻ (54.29%) > Na⁺ (37.14%) > SO₄²⁻ (31.43%) > K⁺ (25.71%) > Mg²⁺ (24.76%) > Ca²⁺ (22.86%) > F⁻ (14.29%) > As (5.71%) > NO₃⁻ (1.90%). Multivariate analysis identified salinity (EC, TDS), bicarbonate, chloride, and sodium as primary influences on GW quality. WQI classification showed only 7.62% of samples as excellent, while most were categorized as poor, with UC Tarai (38.46%) having the highest proportion. The findings highlight critical water quality concerns and threats to public health, emphasizing the need for regular monitoring, water treatment, disinfection, and sustainable utilization of resources to ensure safe drinking water. Keywords: Coastal Sindh, groundwater quality, hydrochemical assessment, multivariate analysis, public health risk, water contamination